2014
DOI: 10.1177/0306312714552347
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology researchers’ collaboration relationships: A gender analysis of access to scientific information

Abstract: Women are underrepresented in STEM fields, particularly at higher levels of organizations. This paper investigates the impact this underrepresentation has on the processes of interpersonal collaboration in nanotechnology. Analyses are conducted to assess: 1) the comparative tie strength of women's and men's collaborations; 2) whether women and men gain equal access to scientific information through collaborators; 3) which tie characteristics are associated with access to information for women and men; and 4) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The relationship between marital status and productivity is complex (Fox, 2005). Focusing on a social network analysis of the nanotechnology field, Villanueva-Felez et al (2015) found that women receive less information from collaborators, enjoy lower levels of tie strength, and tend to use different aspects of social ties in their work, which may also affect productivity. We would be remiss if we did not point out that publication productivity is only one component of the women-in-science story: declining gender gaps in publication productivity do not mean that the problems facing women in academic science are solved (Grant et al, 2000), but gender differences in collaboration may certainly be related to one important outcome of collaboration, publications.…”
Section: Collaboration In Sciencementioning
confidence: 99%
“…The relationship between marital status and productivity is complex (Fox, 2005). Focusing on a social network analysis of the nanotechnology field, Villanueva-Felez et al (2015) found that women receive less information from collaborators, enjoy lower levels of tie strength, and tend to use different aspects of social ties in their work, which may also affect productivity. We would be remiss if we did not point out that publication productivity is only one component of the women-in-science story: declining gender gaps in publication productivity do not mean that the problems facing women in academic science are solved (Grant et al, 2000), but gender differences in collaboration may certainly be related to one important outcome of collaboration, publications.…”
Section: Collaboration In Sciencementioning
confidence: 99%
“…Policy makers need to take account of the fact that the coordination and integration efforts involved in collaborations among heterogeneous actors, may not be gender-neutral [85]. Women's access to scientific information is affected negatively by the smaller number of professional collaborations among women in some scientific areas, and their generally lower status and more junior academic positions [86]. The positive impact on innovation of women in brokerage roles is likely to be reduced by the small presence of women in decision-making positions in institutional scientific settings.…”
Section: Plos Onementioning
confidence: 99%
“…They found that lower publication rates by women were significantly correlated with the amount of research resources typically needed. Last, the lack of professional networks involving women has been identified as a possible detriment to scholarly productivity (Durbin, 2011;Kyvik & Teigen, 1996;Villanueva-Felez, 2015). Indeed, women had fewer coauthors than men (see Figure 4 and Table 6), a pattern that may have contributed to fewer research collaborations and hence scholarly production.…”
Section: Discussionmentioning
confidence: 99%